(untitled) (KYAMC Journal, 2017)
Background: Diabetes is the leading cause of chronic kidney disease which ultimately results end-stage renal disease (ESRD). Objectives: The purpose of the study was to explore the factors influencing or related to the development of the diabetic nephropathy with specific concern to the HbA1c (glycosylated hemoglobin) levels. Methods: Four hundred type 2 diabetic patients (male 166 and female 234) were studied and were evaluated for the presence of nephropathy through the review of their registered diabetic guide book. Glycaemic status was assessed by HbA1c (HbA1c was categorized into 3 groups) and plasma glucose levels. We used Student’s ttest,?2-test and logistic regression analysis to determine and quantify the association of diabetic nephropathy with various risk factors specially HbA1c. Results: The prevalence of nephropathy was 24.0%; male 27.1%, female 21.8%. Increasing HbA1c categories above 7.0% were significantly associated with increased prevalence of nephropathy (15.8 vs 22.8 vs 30.7%; ?2 = 8.590, p = .013). Logistic regression models of univariate analysis showed that the risk of nephropathy was strongly increased at the HbA1c categories 8% (OR = 2.35; 95% CI: 1.30-4.25). Advanced age (OR = 3.8; 95% CI: 2.21-6.53), longer duration of diabetes (OR = 4.05; 95% CI: 2.31-7.10), lacking of physical exercise (OR = 1.93; 95% CI: 1.20-3.10), presence of hypertension (OR = 4.62; 95% CI: 2.42-8.83), fasting blood glucose (OR = 1.139; 95% CI: 1.054-1.231), blood glucose 2 hours after breakfast (OR = 1.088; 95% CI: 1.028-1.152), systolic blood pressure (OR = 1.049; 95% CI: 1.030-1.069) and diastolic blood pressure (OR = 1.061; 95% CI: 1.026-1.097) had significant association with nephropathy. Conclusion: HbA1c categories >7.0% is an important risk factor for the development of nephropathy. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 21-26